Unusual calcified foreign body in ureter - Agarwal, A; Praveen, CR; Pradhan, SK; Belokar, WK (Journal of College of Medical Sciences-Nepal, 2013)
DOI: http://dx.doi.org/10.3126/jcmsn.v8i3.8688 Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-3, 47-50